A comparative study of the clinical benefits of rivaroxaban and dabigatran in patients with nonvalvular atrial fibrillation with high bleeding risk - Liu, Penghui (Frontiers in Cardiovascular Medicine, 2024)
Objective: Rivaroxaban and dabigatran are approved to reduce the risk of stroke in patients with nonvalvular atrial fibrillation(NVAF). However, the clinical benefits of rivaroxaban and dabigatran in people with high bleeding risk are unclear. Methods: A retrospective study was conducted on NVAF patients admitted to the First Affiliated Hospital of Zhengzhou University from May 31, 2016 to May 31, 2019. These patients had a high risk of bleeding and were taking at least one study medication. The aim of the study was to evaluate clinical benefits by comparing the efficacy and safety risks of these two medications Results: Results of the primary efficacy benefit endpoint were obtained from 104 patients (13.21%) in the rivaroxaban group and 81 (15.76%) patients in the dabigatran group (hazard ratio [HR]: 0.860; 95% confidence interval [CI]: 0.637-1.162; P=0.327)，this indicates that there was no significant difference between dabigatran and rivaroxaban in preventing stroke and systemic embolism in patients with high bleeding risk NVAF. The principal safety end points were observed in 49 (6.23%) patients in the rivaroxaban group and in 36 (7.00%) patients in the dabigatran group (HR: 0.801 in the rivaroxaban group; 95% CI: 0.512-1.255; P =0.333)，this indicates that there was no a significant difference in reducing fatal bleeding and critical organ bleeding. With respect to secondary efficacy and benefit endpoints, 28 (3.56%) patients in the rivaroxaban group and 26 (5.06%) patients in the dabigatran group died, with an HR of 0.725 (95% CI: 0.425-1.238; P=0.239); 32 (4.07%) patients in the rivaroxaban group; and 31 (6.03%) patients in the dabigatran group had myocardial infarction (MI), with an HR of 0.668 (95% CI: 0.405-1.102, P=0.114) in the rivaroxaban group, this indicates that there was no significant difference between dabigatran and rivaroxaban in preventing all-cause death and MI. Conclusions: In NVAF patients with high bleeding risk, there was no significant difference between dabigatran and rivaroxaban in preventing stroke and systemic embolism. There was also no significant difference between dabigatran and rivaroxaban in reducing fatal and critical organ bleeding Clinical Trial Registration: Chinese Clinical Trials Registry, identifier ChiCTR2100052454.